Regulations and certification for sustainable bamboo forestry (International Journal of Bamboo and Rattan, 2023)
Nowadays, the growing global awareness is that, if we want to grapple with the impacts of climate change, improve water quality, enhance people's livelihoods, and curb the loss of tropical forest biodiversity, taking good care of our forests is of fundamental importance. As the World population is projected to surpass nine billion by 2050, the global pressure on the world’s tropical forests will continue to grow higher. Likewise, the Living Forests Report by the World Wildlife Fund (WWF) projects that the annual harvesting of wood from forests could be tripled by the middle of the century to meet increased demand for timber products, paper, and bioenergy.
Keywords: World Bamboo Day; sustainable bamboo forestry; Regulations; global awareness; World Wildlife Fund (WWF)